IMPLICATURES IN CHARACTERS’ SPEECH IN PRIDE AND PREJUDICE MOVIE - Desak Putu Eka Pratiwi (LITERA : Jurnal Bahasa Dan Sastra, 2019)
ABSTRACTPeople use spoken language in delivering their purposes. However, their utterancesusually have wider meaning than their literal meaning. This is mostly influenced by the contextwhen the speech occurred and the intention of the speaker. This research is aimed at identifyingimplicatures used by characters in Pride and Prejudice movie in their conversation. The termof ‘implicature’ is used to account for what a speaker can imply, suggest, or mean, as distinctfrom what the speaker literally says. Every utterance said by people does not consist only of aword with its literal meaning but also an intended meaning inside it. People’s intended meaningis mostly tied with the context of time when the utterance is uttered by the speaker. Thissituation makes each person or the hearer possibly have a different interpretation. Therefore, itis important to study language use. In conducting research, the researcher used descriptivequalitative method to identify and describe the implicatures. Observation method was used tocollect the data by watching the movie repeatedly and taking notes the dialogues which haveimplicatures. Then the selected data were analysed by using relevant theory about implicature.The finding shows that there are three types of implicatures in the character’s speech in Prideand Prejudice movie, i.e. (a) conventional implicatures in which the utterances can beautomatically interpreted by the words literally said; (b) generalized conversationalimplicatures in which no special knowledge is required in the context to calculate the additionalconveyed meaning; and (c) particularized conversational implicature in which specific contextis required to make an inference to reach the conveyed meaning.Keywords: conversation, implicature, conventional, generalized, particularizedABSTRAKOrang-orang menggunakan bahasa lisan dalam menyampaikan tujuan mereka.Namun, ucapan mereka biasanya memiliki makna yang lebih luas daripada makna harfiahnya.Ini sebagian besar dipengaruhi oleh konteks ketika pidato terjadi dan niat pembicara.Penelitian ini bertujuan untuk mengidentifikasi implikatur yang digunakan oleh karakterdalam film Pride and Prejudice dalam percakapan mereka. Istilah 'implikatur' digunakanuntuk menjelaskan apa yang disiratkan, disarankan, atau diartikan oleh pembicara, berbedadari apa yang secara harfiah dikatakan oleh pembicara. Setiap ucapan yang diucapkan olehorang-orang tidak hanya terdiri dari sebuah kata dengan makna literalnya tetapi juga maknayang dimaksudkan di dalamnya. Makna yang dimaksudkan orang sebagian besar terikatdengan konteks waktu ketika ucapan itu diucapkan oleh pembicara. Situasi ini membuat setiaporang atau pendengar mungkin memiliki interpretasi yang berbeda. Karena itu, penting untukmempelajari penggunaan bahasa. Dalam melakukan penelitian, peneliti menggunakan metodedeskriptif kualitatif untuk mengidentifikasi dan menggambarkan implikasinya. Metode mencatat dialog yang memiliki implikasi. Kemudian data yang dipilih dianalisis denganmenggunakan teori yang relevan tentang implikatur. Temuan ini menunjukkan bahwa ada tigajenis implikatur dalam pidato karakter dalam film Pride and Prejudice, yaitu (a) implikaturkonvensional di mana ucapan dapat diinterpretasikan secara otomatis oleh kata-kata yangdiucapkan secara harfiah; (B) implikatur percakapan umum di mana tidak ada pengetahuankhusus diperlukan dalam konteks untuk menghitung makna yang disampaikan tambahan; dan(c) implikatur percakapan khusus di mana konteks spesifik diperlukan untuk membuatkesimpulan untuk mencapai makna yang disampaikan.Kata kunci: percakapan, implikatur, konvensional, percakapan umum, percakapan khusus